Basel II Accord and the Business Models of Banking Institutions in Malaysia:The Case Study of Local Banking Institutions - Talib, Norashikin (2005)
Banking Institutions have been regarded as conservative and safe institutions for investors as they are highly regulated. As the financial markets increase in complexity as a result of the development of a more complex financial instruments enabled by technological advancement, the changes in the current approach in capital adequacy assessment (known as Basel I Accord) need further enhancement, hence lead to the birth of Basel II Accord. The migration to Basel II is inevitable as it does not only contain the methodology for capital compliance, but also it provides avenues for banking institutions to build and adopt a more robust risk management framework in the course of weathering business challenges prevailing in the sophisticated world of banking. The Basel II Accord enables the banks to build and adopt a robust risk management to protect the banks vis-à-vis the investors. A classic case is noted in the case of Barrings Bank which collapsed due to lack of internal controls. The substantial losses incurred by The National Australia Bank in Year 2004 due to foreign exchange (forex) option losses were another example of inferior risk management framework. However, so far, there is no explicit implication in terms of the expected business model to be adopted by banking institutions following the adoption of Basel II Accord. This research paper is trying to establish the potential business models that would be adopted by local banking institutions in Malaysia following the adoption of Basel II Accord. The survey conducted on the local banking institutions in Malaysia favoured in moving towards Standardised Approach. This is understandable given the existing infrastructure, resources and systems in the local banking institutions. However, there are also on-going initiatives by some institutions to migrate towards a more sophisticated approach to gain a competitive advantage against their competitors. There is no one-size-fit-all approach. The business models of the local banking institutions are driven by the respective banks’ Business Plans and their risk tolerance levels.